Anchor Groups for Graphene‐Porphyrin Single‐Molecule Transistors. (14th September 2018) - Limburg, Bart; Thomas, James O.; Holloway, Gregory; Sadeghi, Hatef; Sangtarash, Sara; Hou, Ian Cheng‐Yi; Cremers, Jonathan; Narita, Akimitsu; Müllen, Klaus; Lambert, Colin J.; Briggs, G. Andrew D.; Mol, Jan A.; et al.
Abstract: The effectiveness of five different anchor groups for non‐covalent interfacing to graphene electrodes are compared. A family of six molecules is tested in single‐molecule junctions: five consist of the same porphyrin core with different anchor groups, and the sixth is a reference molecule without anchor groups. The junction formation probability (JFP) has a strong dependence on the anchor group. Larger anchors give higher binding energies to the graphene surface, correlating with higher JFPs. The best anchor groups tested are 1, 3, 8‐tridodecyloxypyrene and 2, 5, 8, 11, 14‐pentadodecylhexa‐ peri ‐hexabenzocoronene, with JFPs of 36% and 38%, respectively. Many junctions are tested at 77 K for each molecule by measuring source‐drain current as a function of bias and gate voltages. For each compound, there is wide variation in the strength of the electronic coupling to the electrodes and in the location of Coulomb peaks. In most cases, this device‐to‐device variability makes it impossible to observe trends between the anchor and the charge‐transport characteristics. Tetrabenzofluorene anchors, which are not π‐conjugated with the porphyrin, exhibit different charge transport behavior to the other anchors tested, and they show multiple Coulomb peaks with characteristically small molecular electron‐addition energies of 0.3–0.7 eV, whereas the other compounds give single Coulomb peaks. Abstract : Molecules can be interfaced with graphene electrodes using non‐covalent interactions to generate single‐molecule transistors . A family of π‐stacking anchor groups is synthesized and the yield of transistors depends strongly on the nature of the anchor group. Whilst coupling to electrodes varies between devices, it is possible to identify junctions functionalized with single molecules if they exhibit characteristic addition energies.